Mental health and its wider determinants in young people in the UK during 12 months of the COVID-19 pandemic: repeated cross-sectional representative survey - Olivier Y. Rouquette; Dana Dekel; Abdul-Moiz Siddiqi; Catherine Seymour; Lauren Weeks; Ann John (BJPsych Open)
Background The COVID-19 pandemic posed an unprecedented global challenge, with past evidence suggesting negative psychological effects with the additional concern that social and physical restrictions might disproportionately affect adolescents.